Mid90s [videorecording (DVD)] - Hill, Jonah, 1983-; Suljic, Sunny, 2005-; Hedges, Lucas, 1996-; Smith, Na-kel (Lions Gate Entertainment, 2019)
The story of Stevie, a teenager growing up in Los Angeles. He struggles with his family, including his abusive old brother and co-dependent single mom. He also struggles with his richer friends at school. When Stevie befriends a crew of skateboarders, he learns some tough lessons about race, class, and privilege.